Relative growth of freshwater prawn Macrobrachium brasiliense (Decapoda, Palaemonidae) and its implications for reproduction - Nogueira, Caio dos Santos [UNESP]; Oliveira, Marcela Silvano de; Jacobucci, Giuliano Buza; Almeida, Ariadine Cristine de (Fundacao Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2019)
The main objective of this study was to estimate the morphological sexual maturity of Macrobrachium brasiliense (Heller, 1862) and to analyze the relative growth of the species. During one year of sampling, from July 2012 to June 2013, 199 specimens were collected in a stream located in a Cerrado biome, in the Triangulo Mineiro region, state of Minas Gerais. Once identified and sexed, the length of the carapace, the length of the segments of the chelipeds (ischium, merus, carpus, propodus and dactyl) and width of the pleura were measured (mm). The maximum and mean sizes of the carapace length measured 20.5 mm (Mean: 9.6 +/- 4.2 mm) and 20.1 mm (Mean: 7.7 +/- 3.4 mm) for males and females, respectively. The propodus length for males, and the pleura width for females, were used for the classification of the specimens into juvenile and adult, using K-means analysis and discriminant analysis. The relative growth of the species was also evaluated through covariance analysis for all structures (ANCOVA, alpha = 0.05). In females, the growth of most structures occurred equally between juveniles and adults, with the exception of the merus and pleura structures. On the other hand, the growth of almost all structures of males differed between juveniles and adults. Only the carpus and the pleura growth were similar. We also estimated the size at onset of morphological sexual maturity at 8.64 mm CL for males (CL50%,r = 1.71) and 8.03 mm CL for females (CL50%, r = 0.07). Our results contribute to the understanding of some important questions related to the reproductive biology of M. brasiliense. We noted that males grow differently from females and become the largest individuals in the population, resulting in a sexual dimorphism. Such sexual dimorphism might promote the development of the temporary mating guarding behavior, a reproductive strategy very important for caridean shrimps.
Keywords: Allometry; morphological sexual maturity; reproductive biology